The Role of Culture in The Continued Practice of Female Genital Mutilation: A Study of Attah Community, Imo State - Ajaegbu, Okechukwu (Universitas Djuanda, 2024)
Even though the practice of female genital mutilation is not meant to hurt women, it nonetheless endangers their health. This necessitates research into the amount of understanding and cultural complications that prevent its eradication in Africa and Nigeria, particularly in rural communities where the practice is very prevalent. This study, therefore, examined cultural factors that promote the continued practice of female genital mutilation in the Attah community, Imo State. Social convention theory was used as the study's theoretical framework. The survey research method was adopted for this study. Using the multi-stage sampling method, 674 copies of the questionnaire were distributed to the study respondents for the quantitative data. However, only 539 copies of the questionnaire were retrieved. This represents the sample size of this study. For the qualitative data in the study, twelve (12) in-depth interviews were conducted among village and religious leaders. Statistical Package for Social Science (SPSS) was used to process this study's quantitative data, while descriptive and inferential statistics were analyzed. For the study's qualitative data, analysis was done using the content analysis method based on the study objectives. It was found that males are more likely to make decisions that influence the continued practice of Female Genital Mutilation in the Attah community than females. The study also found that cultural expectations for womanhood rite of passage, marriage prospects, and the belief that women with FGM are more likely to be less promiscuous are major factors that influence the continued practice of FGM in the Attah community. Consequently, to end female genital mutilation in the Attah community, there is a need to address those religious and cultural beliefs that negatively affect the control of the practice.